EKSTRAK CACING TANAH SEBAGAI INOVASI PENYEMBUHAN ULKUS DIABETIK BERBASIS INDUKSI DENSITAS AKSON - Mardiati, Ni Putu Jeny; Yunitasari, Arinda Nur; Sari, Dwi Astika; Saraswasta, I Wayan Gede; Putra, Fetreo Negeo; Kristianto, Heri (Program Kreativitas Mahasiswa - Penelitian, 2013)
Reduction of nerve growth factor expression in diabetic ulcer affects overall wound healing. Earthworm (Pheretima aspergillum) can stimulate schwann cell proliferation and migration to support axonal elongation. The objective of this study is to compare wound healing functions in diabetic ulcer of rats using earthworm extract, hydrogel, and conventional dressing. This study applied a true-experimental posttest only controlled group design. 21 days after treatment, the group receiving earthworm extract had a significantly higher percentage of wound contraction and axonal density compared to the control group (p<0.05). These results show that earthworm extract can promote wound healing in diabetic ulcer.Â Keywords: Diabetic Ulcer, Earthworm (Pheretima aspergillum), Wound Contraction, Peripheral Nerve Regeneration.